When companies don't die: Analyzing zombie firms in a low interest rate environment - Angela De Martiis; Franziska J. Peter (Aussenwirtschaft, 2023)
We examine whether low interest rates foster non-viable firms in Europe by analyzing two classes of firms: zombies and distressed. Controlling for the business cycle and recession periods, we find a significantly negative effect of short-term rates on the likelihood of being a zombie, while no effect for distressed firms is detected. A decrease in inflation and a lower state of the business cycle is associated with a rise in both zombies and distressed firms. Examining a non- conventional monetary policy program, we find no evidence of credit misallocation. Therefore, concurring monetary and macroeconomic phenomena likely explain the presence of non-viable firms, although with dissimilarities between zombies and distressed firms.
Keywords: D22; E32; E43; E52; G33; 330; zombie firms; distressed firms; monetary policy; business cycle